Claire Mix posing with the American Flag - Sahl, Ted (photographer):::Creator::::::::::::
Photograph is a portrait of Claire Mix reclining on the floor, propped up on her elbow with a pair of sunglasses held in front of her body in her right hand. The American Flag is draped over her right shoulder and left leg.